Lanthanide doping enabled multimodal luminescence in layered lead-free double perovskite Cs4MnBi2Cl12. Issue 19 (29th April 2022) - Li, Jingyu; Xiao, Jiawen; Lin, Taifeng; Yan, Zhengguang; Han, Xiaodong
Abstract : Doping lanthanide ions into the Cs4 MnBi2 Cl12 double perovskite results in multimodal luminescence, and the unique Bi–Mn–Bi sandwich structure facilitates the energy transfer between the transition metal ions and lanthanide ions. Abstract : The incorporation of lanthanide ions (Ln 3+ ) has been shown to be an effective strategy to tune the luminescence properties in lead-free halide double perovskites. However, most Ln 3+ -doped double perovskites exhibit a low luminescence efficiency and a high excitation energy and/or require doping with multiple ions which result in complex compositions. Herein, we demonstrate that the Ln 3+ doping (Ln = Yb, Er, Nd) in the layered double perovskite Cs4 MnBi2 Cl12 enables multimodal luminescence, that is, the orange-red emission from the d–d transition of Mn 2+, the efficient ultraviolet light excited near-infrared (NIR) emissions of Ln 3+ and the upconversion emissions in both Yb- and Yb/Er-doped systems. In addition, the NIR emissions of Ln 3+ can also be excited by blue and green light benefiting from the energy transfer from Mn 2+ to Ln 3+ . Finally, taking advantage of the multimodal luminescence in the Ln 3+ -doped Cs4 MnBi2 Cl12 phosphor, a preliminary anti-counterfeiting application is demonstrated. We highlight that the particular chemical composition (comprising Bi 3+ and Mn 2+ ) and the sandwich-type Bi–Mn–Bi layered crystal structure facilitate the light absorption and the energy transfer from Bi 3+ to Ln 3+ and Mn 2+ to Ln 3+, demonstrating the importance of the rational selection and design of double perovskite host materials for Ln 3+ doping.